Intervensi Konseling Individual dan Kelompok untuk Mengatasi Kesulitan Pertemanan pada Siswa SMA: Studi Kasus Pendekatan Integratif - Syakhila Takhira; Putri Nuriandini; Nurnajhiha Izzati; Donal (Indo Publishing, 2025)
This study aims to provide an in-depth understanding of the factors influencing a Grade X student’s difficulties in peer relationships and to examine the effectiveness of individual counseling and group counseling interventions in addressing these issues. Using a qualitative case study design, the research involved one primary student participant, supported by classmates and a school counselor as additional informants. Data were collected through in-depth interviews, observations, and documentation, and analyzed using Miles, Huberman, and Saldaña’s analytical model. The findings reveal that the student’s social challenges stem from an interplay of internal factors such as withdrawal tendencies and low self-confidence and external factors related to negative peer perceptions and group dynamics. The individual counseling sessions facilitated self-awareness and improvement in basic communication skills, while group counseling provided emotional support and opportunities for social learning through direct peer interaction. Both interventions proved effective in enhancing the student’s social adjustment and preventing maladaptive coping strategies, such as the desire to transfer to another class. These findings underscore the importance of integrated school counseling approaches in helping students overcome social relationship barriers